Transformational Leadership of School Principals in Building Organizational Learning at Islamic Boarding School Vocational Schools - Zainal Abidin; Ahmad Qusairi; Fadhel Mubarak (ADARA, 2026)
This study aims to analyze the transformational leadership mechanisms of principals in building organizational learning in Islamic boarding schools (SMK Pesantren). The study used a qualitative approach with a case study design. Data were collected through in-depth interviews, participant observation, and documentation studies over six months, then analyzed using iterative thematic analysis techniques. The results show that organizational learning is formed through a multi-layered process that begins with moral legitimacy based on religious values, followed by the development of a participatory vision, the creation of a collective reflective space, and systematic individual development. Transformational leadership functions not only as a leadership style but also as a transformation mechanism that integrates institutional values ​​with modern managerial practices. These findings extend the educational leadership literature by demonstrating that the effectiveness of transformational leadership in the context of Islamic boarding schools is strengthened by moral legitimacy and collective culture. This study contributes theoretically through a processual model that explains the relationship between transformational leadership and organizational learning and practically provides a strategic framework for strengthening the organizational capacity of value-based schools.